Pengaruh Kepuasan Kerja Terhadap Kinerja Karyawan CV. Diagram Global Mandiri Manado - Londok, Ribkha Novelin; Areros, William Agustinus; Asaloei, Sandra (Sam Ratulangi University, 2019)
The purpose of the results of this study was to find that there were eighteen samples of male sex and twelve samples of female sex. most work thirty-one years. From the test results it was found that the results of simple linear regression were 16.607. regression direction coefficient of 0.590 states that each addition of 1% value X, then the value of Y is 0.590. the regression direction coefficient is positive. and get a significant value (p-value) of 0.004. can be concluded that job satisfaction affects the performance of employees in the company CV. Manado Independent Global Diagram. Based on the results above, the significance value is 0.004. it can be concluded that the independent variable has significant influence on the dependent variable. The results of this study can answer the hypothesis that job satisfaction is influential on the performance of CV employees. Manado Global Self Chart.